EVALUASI UJI KLON JATI (Tectona grandis L.f.) UMUR 20 TAHUN DI KPH CEPU PERUM PERHUTANI - Deanova Frestiana Br Pelawi; Sapto Indrioko; Fanny Hidayati; Aris Wibowo (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2020)
Evaluation of the teak clone test aims to determine the growth and genetic parameters of the clones at the age of 20 years. Teak clone test was established in 1999 with a Randomized Complete Block Design (RCBD). The number of clones used was 65 clones, five replications (blocks), four treeplots, with a spacing of 3m x 3m. Measurements were carried out on the growth characteristics (i.e., plant height and diameter at breast height / DBH) and wood quality (i.e., Pilodyn penetration stress-wave velocity / SWV). The results of the analysis of variance showed that there were very significant differences in all observed growth characteristics. Heritability for plant height, stem diameter, Pilodyn penetration, and SWV were 0.38, 0.51, 0.59, 0.29, and 0.53, respectively. The expected genetic gains for volume and SWV were 21.81% and 2.11%, respectively, by selecting the best seven clones. The correlation between growth characteristics and between wood quality with growth characteristic is positive, indicating that improvement in productivity is followed by wood quality. The best clones based on clone values of stem diameter and SWV characteristics are clones number 110, 24, 97, 108, 20, 35, and 31, respectively.